A quantitative method for ISO 17799 gap analysis - Karabacak, Bilge; Soğukpınar, İbrahim (Elsevier Advanced Technology, 2006)
ISO/AEC 17799:2005 is one of the leading standards of information security. It is the code of practice including 133 controls in 11 different domains. There are a number of tools and software that are used by organizations to check whether they comply with this standard. The task of checking compliance helps organizations to determine their conformity to the controls listed in the standard and deliver useful outputs to the certification process. In this paper, a quantitative survey method is proposed for evaluating ISO 17799 compliance. Our case study has shown that the survey method gives accurate compliance results in a short time with minimized cost. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: BS 7799; ISO 17799; ISO 27001; compliance; information security; risk analysis; quantitative risk analysis; survey